2017
DOI: 10.1038/s41598-017-03017-z
|View full text |Cite
|
Sign up to set email alerts
|

Lethal effect of blue light on strawberry leaf beetle, Galerucella grisescens (Coleoptera: Chrysomelidae)

Abstract: In a previous study, we found that blue-light irradiation kills insects such as fruit flies, mosquitos, and flour beetles. However, the lethal effects of blue light on coleopteran field crop pests have not been investigated. Chrysomelidae, a major family in phytophagous beetles, includes many species of crop pests. We investigated the lethal effect of blue light on chrysomelid beetles by examining the mortality of the strawberry leaf beetle Galerucella grisescens irradiated with different wavelengths of blue l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Our group is investigating the relationship between the lethal effects of blue light and developmental stages for over 10 insect species, such as Galerucella grisescens , Clogmia albipunctatus , Liriomyza sativae , and so on. For example, the eggs of Galerucella grisescens , the strawberry leaf beetle, are killed by irradiation at 438 nm; however, the pupae are not killed by this wavelength [ 28 ]. This previous report [ 28 ] only compared eggs and pupae, but the results suggest that the photosensitivity of other holometabolous insects might also change, depending on the stage of development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group is investigating the relationship between the lethal effects of blue light and developmental stages for over 10 insect species, such as Galerucella grisescens , Clogmia albipunctatus , Liriomyza sativae , and so on. For example, the eggs of Galerucella grisescens , the strawberry leaf beetle, are killed by irradiation at 438 nm; however, the pupae are not killed by this wavelength [ 28 ]. This previous report [ 28 ] only compared eggs and pupae, but the results suggest that the photosensitivity of other holometabolous insects might also change, depending on the stage of development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the eggs of Galerucella grisescens , the strawberry leaf beetle, are killed by irradiation at 438 nm; however, the pupae are not killed by this wavelength [ 28 ]. This previous report [ 28 ] only compared eggs and pupae, but the results suggest that the photosensitivity of other holometabolous insects might also change, depending on the stage of development. In comparison, our preliminary experiments suggest that the effective wavelength of certain insects does not change with development, as observed for Culex pipiens molestus (unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…Hori and colleagues revealed that blue light can kill some household pests and field crop pests (Hori et al, 2014; Hori and Suzuki, 2017). Insect species Drosophila melanogaster , Culex pipiens molestus , Tribolium confusum , and Galerucella grisescens , and wavelengths 407, 417, 438, and 465 nm were studied.…”
Section: Potential New Applications Of Antimicrobial Blue Lightmentioning
confidence: 99%
“…It was shown that the effective wavelengths of blue light were species-dependent and growth-stage-dependent (e.g., egg stage, pupal stage, etc.). The lethal effect of blue light on insects was thought to be attributed to the ROS produced by the blue light excitation of endogenous photosensitizers in the insect tissues (Hori and Suzuki, 2017). The ROS damaged the tissues and killed the insects.…”
Section: Potential New Applications Of Antimicrobial Blue Lightmentioning
confidence: 99%
“…The peak wavelength of LED and xenon flashes is in the blue region of visible light (400-480 nm) that could adverse biological effects including human eyes and skin when receiving long exposure [25]. The toxic effects of short wavelength light on many insects are known, i.e., mortality in immature stages of D. melanogaster [26] and strawberry leaf beetle [27]. In case of fireflies, the short wavelength of light caused flash signal alteration mentioned by the researchers [12].…”
Section: Discussionmentioning
confidence: 99%